Influence of Occupational Physical Activity on Anthropometric Profile and Body Composition of Bricklayers in Kwara state, Nigeria - Dominic Olufunmilola Leah; Etchie Aboyowa Omokwa; Seidina Iliasu Yakubu; Niyi-Odumosu Faatihah Adeyinka; Owolabi Florence (Sapientia Publishing Group, 2018)
Objectives Optimal amount of muscle and fat mass has been associated with level of physical activity and are basic determinants of individuals' health, fitness including occupational performance. The study determined the level of occupational physical activity and influence on anthropometrics, body composition and health of bricklayers in Kwara state, Nigeria. Methods Descriptive correlational design was used. During the study only three bricklaying sites were functional and all the 45 bricklayers who met the inclusion criteria were purposively selected. Standardized instruments: non-elastic anthropometric tape rule, stadiometre and weight scale were used for anthropometric and body composition measurement while Occupational Physical Activity Questionnaire (OPAQ; r = .72) was used to assess work-related physical activity. Pilot test was conducted to confirm calibration and functionality of body composition equipment. Informed consent was sought from the participants with ethical approval obtained from the Institutional board. Statistical analysis was performed using SPSS V20.0 with descriptive statistics of mean and standard deviation for analyses of body composition and physical activity while inferential statistics of PPMC and t-test were for analysis of hypotheses at a 0.05 alpha level. Results Participants performed vigorous intensity occupational physical activity expending an average of 2,699.1 MET-min∙wk-1. Occupational physical activity negatively correlated with their body mass index (N = 45, r = -.06, r2 = .36%, p = .05); Waist circumference (N = 45, r = -.083, r2 = .69%, p = .05) and positively correlated with their bicep circumference (N = 45, r = .61, r2 = 37.2%, p = .001) and chest circumference (N = 45, r = .40, r2 = 16%, p = .007). Conclusions Bricklaying positively influenced body parameters which might induce health and fitness benefits. However, there is need for health promotion intervention for enlightenment and healthy life-style practice among bricklayers to improve overall health and fitness.